Back Cover: Detection, prevention and treatment of COVID‐19 and opportunities for nanobiotechnology (View 4/2022). Issue 4 (25th July 2022) - Bao, Qing; Yang, Tao; Yang, Mingying; Mao, Chuanbin
Abstract : In article number 20200181, Chuanbin Mao, Mingying Yang and their co‐wokers have demonstrated that nanobiotechnology holds promise for combating COVID‐19. It provides nanoscale probes to detect COVID‐19, nanoscale vaccines to prevent COVID‐19, and nanoscale therapeutics to treat COVID‐19. Because nanoparticles are comparable to the virus particles that cause COVID‐19, the nanoparticles can be engineered to detect, prevent or treat COVID‐19 in a more efficient manner than the other agents.